Prevalence and Diffusion of Gastrointestinal Parasite Infections in Swamp Water Buffalo (Bubalus Bubalis) Populations from Marshlands of Iraq - Al-Jubury, Azmi; Jarullah, Basim A.; Al-Jassim, Khawla B.N.; Badran, Methaq; Mahmmod, Yasser S. (Journal of Buffalo Science, 2020)
Background and objectives: New information on the epidemiology of gastrointestinal (GI) parasite infection in water buffaloes is crucial for understanding their risk factors and transmission. The objectives of this study were (1) to determine the prevalence of GI parasites in buffaloes in the Marshland areas of southern Iraq, and (2) to evaluate the association of risk factors with the parasitic infections. Materials and Methods: A total of 166 water buffaloes from the Marshland in the north of Basra (n=75), and Thi-Qar (n=91) provinces from November 2016 to April 2017 were enrolled. Fecal samples were collected and examined for the presence of helminth eggs and protozoal oocysts using sedimentation-flotation and centrifugal flotation techniques. Results: The overall prevalence of infection in buffaloes was 82% (136/166), with the highest number of single parasite infection (64%), followed by those with double (29%) and triple (7%) parasite infections. The most frequently identified parasites were Fasciola spp. (23%, 39/166), Eimeria spp. (19%, 32/166), Toxocara vitulorum (13%, 21/166), Trichostrongylus spp. (12%, 20/166), and Oesophagostomum spp. (10%, 10/166). Moniezia spp. was the only identified cestode with a prevalence of (8%, 13/166). A significant association was reported between feeding type and parasitic infections with Eimeria spp., Trichostrongylus spp., Moniezia spp., Trichuris spp., and Ostertagia ostertagia. Conclusion: The prevalence of GI parasitic infection in buffaloes raised in the Marshlands is high, indicating a high intensity of natural infection. The findings of this study imply an urgent need for the implementation of efficient control measures against parasitic infections in the Marshlands.